Tuning the hybridization and charge polarization in metal nanoparticles dispersed over Schiff base functionalized SBA-15 enhances CO2 capture and conversion to formic acid - Cherevotan, Arjun; Ray, Bitan; Yadav, Anish; Bagchi, Debabrata; Singh, Ashutosh Kumar; Riyaz, Mohd; Churipard, Sathyapal R.; Naral, Vinay; Kaur, Komalpreet; Gautam, Ujjal K.; Vinod, Chathakudath P.; Peter, Sebastian C. (Journal of Materials Chemistry A, 2022)
Different Schiff base functionalized SBA-15 materials were synthesized through condensation reactions between 3-aminopropyltriethoxysilane (APTES) and different aldehydes (glutaraldehyde and butyraldehyde) over a mesoporous silica, SBA-15 (APTES-GLU/SBA-15 and APTES-BUT/SBA-15). Both static and dynamic experiments have been used for testing the CO2 capture efficiency of these materials. The hybridization of the N atom in APTES has been tuned from sp(3) to sp(2) upon condensation facilitating optimum CO2 capture in the direct synthesis of APTES-GLU/SBA-15. The undesirable oxides of nitrogen have been removed during the synthesis process to improve the CO2 capture efficiency. These materials were employed as supports for Pd-Ag and Pd-Ni bimetallic systems for the selective conversion of the captured CO2 to formic acid (FA) in 0.5 M KHCO3 solution. The Pd-Ni catalyst system exhibited enhanced CO2 to FA conversion activity compared to other heterogeneous systems, which is similar to 4 times better than that of the Pd-Ag system in this study. The X-ray absorption studies over the catalyst material confirmed that the relatively electron-deficient Ni in Pd-Ni compared to Ag in Pd-Ag favoured higher charge polarization between the metals in the Pd-Ni system enhancing the CO2 to FA conversion. The experimental observations are well supported by the DFT calculations.

Metal deficiency tuned charge transfer in intermetallic Ni2-xSn (x =0.37-0.65) enhances selective conversion of furfural to furfuryl alcohol towards the theoretical limit - Cherevotan, Arjun; Singh, Ashutosh Kumar; Yadav, Anish; Maligal-Ganesh, Raghu V.; Raj, Jithu; Pulparambil, Anu; Goud, Devender; Vinod, Chathakudath P.; Peter, Sebastian C. (Journal of Materials Chemistry A, 2025)
Heterogeneous catalysis facilitated by intermetallic nanoparticles has recently been the subject of increased scrutiny, given the enhanced selectivity and stability they bestow on many chemical reactions compared to their monometallic components. This paper explores a series of Ni-Sn (Ni2-xSn, where x = 0.65, 0.5, 0.37) intermetallic compounds supported on a high-surface-area support, SBA-15, as catalysts for the selective hydrogenation of furfural to furfuryl alcohol. Rietveld refinements of the X-ray diffraction data show catalysts with mixed intermetallic phases that assist in the catalysis. At the same time, X-ray photoelectron spectroscopy (XPS) studies and X-ray absorption studies indicate the role played by charge transfer from Sn to Ni for the catalysis. Selectivity to the desired furfuryl alcohol in all the intermetallic samples was high (>97%), but Ni1.35Sn had a relatively lower conversion than the other intermetallic compounds.